First record of Bursaphelenchus hildegardae Braasch et al., 2006 (Nematoda) in New Zealand with updated information on morphology, sequencing and a key to species of the eggersi-group - Zhao, Zeng Qi; Surrey, Michael; Ho, Wellcome; Marinov, Milen; Bleach, Carolyn; Rogan, Brent; Alexander, Brett (Zootaxa, 2021)
Bursaphelenchus hildegardae Braasch et al., 2006 was collected from pine wood (Pinus radiata) growing in Kaingaroa Timberlands, and a bark beetle, Hylastes ater Paykull, 1800 in New Zealand. This is a new record for B. hildegardae, occuring in New Zealand, and the second report from the southern hemisphere in addition to Australia. In general, the New Zealand isolate of B. hildegardae corresponds well with the description of B. hildegardae given by Braasch et al. (2006) from Germany. The New Zealand isolate is characterized by having an adult body length of 807–1190 μm, medium a ratios (47.5–58.5 for female and 44.6–60.1 for male), b ratios of 9.8–14.5 (female) and 10.2–12.7 (male), c ratios of 18.8–25.2 (female) and 21.6–32.4 (male), c’ ratios of 4.0–4.4 (female) and 2.1–2.7 (male), and is characterised by having three incisures in the lateral fields, thorn-shaped spicules with a distinctly dorsally-bent thin hook-like condylus, and a dorso-ventally visible terminal bursa. In addition, molecular phylogeny using near full length small subunit (SSU), D2/D3 expansion segments of the large subunit (LSU) and the internal transcribed spacer region (ITS1 and 2) of the ribosomal rDNA supports the identification. A key to Bursaphelenchus species in the eggersi-group is given.